Development of High Clearance Power Sprayer for Cotton - Mahal, J S; Garg, I K; Sharma, V K; Dixit, A K (Journal of Agricultural Engineering, 2007)
A self-propelled high clearance sprayer for spraying on cotton crop was developed. The sprayer is powered by a two cylinder 20 hp diesel engine and has a ground clearance of 1200 mm. Maximum road speed of the sprayer is 20 km/h and can be operated at field speeds upto 5 km/h. The boom width of the sprayer is 8.87 m with 14 nozzles spaced at 67.5 cm. Effective width of coverage is 9.45 m. Boom height can be adjusted from 315 mm to 1685 mm to suit different crops heights. Machine's track width is 1320 mm. During operation two rows of cotton crop come under the machine chassis. The tank capacity is 1000 Litres sufficient to cover 4 ha with one filling. The machine can cover an area of 2 ha/h and the tank is refilled every two hours. Tank refilling time is about 30-45 min depending upon the distance of water source. Mechanical damage caused by the movement of high clearance sprayer was less than that caused by commonly used tractor operated sprayers. Average yield obtained from area sprayed by high clearance sprayer was 10% higher than the area sprayed by tractor operated sprayer.